Towards practical quantum computers: transmon qubit with a lifetime approaching 0.5 milliseconds - Wang, Chenlu; Li, Xuegang; Xu, Huikai; Li, Zhiyuan; Wang, Junhua; Yang, Zhen; Mi, Zhenyu; Liang, Xuehui; Su, Tang; Yang, Chuhong; Wang, Guangyue; Wang, Wenyan; et al. (npj quantum information, 2022)
Here we report a breakthrough in the fabrication of a long lifetime transmon qubit. We use tantalum films as the base superconductor. By using a dry etching process, we obtained transmon qubits with a best T 1 lifetime of 503 μs. As a comparison, we also fabricated transmon qubits with other popular materials, including niobium and aluminum, under the same design and fabrication processes. After characterizing their coherence properties, we found that qubits prepared with tantalum films have the best performance. Since the dry etching process is stable and highly anisotropic, it is much more suitable for fabricating complex scalable quantum circuits, when compared to wet etching. As a result, the current breakthrough indicates that the dry etching process of tantalum film is a promising approach to fabricate medium- or large-scale superconducting quantum circuits with a much longer lifetime, meeting the requirements for building practical quantum computers.